Confluence thanks to extensional determinism - Roscoe, A (Elsevier, 2006)
A process is extensionally deterministic if, after any trace s and given any event a, it is either certain to accept or certain to refuse a (stably) after s. We show how several process algebras are capable of expressing this property and how they agree on the equivalence of deterministic processes. A number of important properties of processes P, including confluence, can be captured in terms of the determinism of some context C[P].